2009
DOI: 10.1002/mds.22765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of weight gain and energy intake after subthalamic versus pallidal stimulation in Parkinson's disease

Abstract: To compare body mass index (BMI) and daily energy intake (DEI) after subthalamic versus pallidal deep brain stimulation (DBS). Weight gain following DBS in Parkinson's disease patients remains largely unexplained and no comparison of subthalamic and pallidal (GPi) stimulation has yet been performed. BMI and DEI, dopaminergic drug administration and motor scores were recorded in 46 patients with PD before STN (n = 32) or GPi (n = 14) DBS and 3 and 6 months after. At M6, BMI had increased by an average of 8.4% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 33 publications
7
61
1
Order By: Relevance
“…Nevertheless, 2 patients of our small study cohort experienced relevant psychiatric side effects and a significant increase of body weight and BMI was also observed over the entire group which is in line with previous reports [7,41]. Moreover, global cognitive functioning measured with the MDRS deteriorated in our DBS cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, 2 patients of our small study cohort experienced relevant psychiatric side effects and a significant increase of body weight and BMI was also observed over the entire group which is in line with previous reports [7,41]. Moreover, global cognitive functioning measured with the MDRS deteriorated in our DBS cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with the Globus pallidum (GP), the Subthalamic Nucleus (STN) is more strongly associated with weight gain, even if not all studies are consistent with this finding (Mills, Scherzer, Starr, & Ostrem, 2012;Sauleau et al, 2009 but see Locke et al, 2011;Volkmann et al, 2001).…”
Section: Weight Food Intake and Deep Brain Stimulationmentioning
confidence: 99%
“…Recently, it has been proposed to name eating abnormalities after DBS "hypo-dopaminergic snacking" rather than Binge Eating, thus emphasizing the role of dopaminergic reduction in the occurrence of these abnormalities (Kistner et al, 2014). As a final remark, the majority of the studies do not report an increase in food intake among PD patients with DBS or an improvement in appetite or change in eating habits (Bannier et al, 2009;Macia et al, 2004;Montaurier et al, 2007;Perlemoine et al, 2005;Rieu et al, 2011;Sauleau et al, 2009) but few studies report such findings (Jorgensen, Werdelin, Lokkegaard, Westerterp, & Simonsen, 2012;Nirenberg & Waters, 2006). However, as we have already argued in this review, the evaluation of food intake, via self-reported measures, may be imprecise and inaccurate.…”
Section: Weight Food Intake and Deep Brain Stimulationmentioning
confidence: 99%
“…Studies showed a significant weight gain both in patients who have undergone unilateral pallidotomy or pallidal stimulation and in those who have undergone stimulation of the subthalamic nucleus [25][26][27]. However, recently Sauleau et al, compared the effect of setting in place deep brain stimulation in the subthalamic position (STN) and the pallidal position (GPi) on weight gain and BMI, in 46 patients with PD.…”
Section: Weight Gain and Dbs Of The Globus Pallidusmentioning
confidence: 99%